VALUE-BASED FIRM PERFORMANCE ANALYSIS USING EVA, MVA, AND FVA: EVIDENCE FROM PT ADHI KARYA (PERSERO) TBK - Haryati, Sany; Agoes Hari Edy Wibowo; Fajri Ramadhani (Bajang Institute, 2026)
Firm value creation constitutes a central objective of modern financial management, particularly for publicly listed companies operating in capital-intensive industries. This study aims to examine firm value creation at PT Adhi Karya (Persero) Tbk by applying value-based performance measurement indicators, namely Economic Value Added (EVA), Market Value Added (MVA), and Financial Value Added (FVA). The research employs a quantitative descriptive approach using secondary data derived from audited annual financial statements and stock market information over the 2021–2023 period. The findings reveal that EVA and FVA values remain consistently positive, indicating that the company has been able to generate internal economic and financial value. However, MVA values are persistently negative, suggesting that the capital market has not fully recognized the firm’s internal value creation. These results imply a divergence between internal performance and market perception. This study contributes to the literature on value-based financial management by providing empirical evidence from Indonesia’s construction sector and highlights the importance of integrating internal value creation with effective market communication strategies.